Collaborative and co-Ordinated action for Medication Safety (COMS): Experience-based co-design of an intervention blueprint to improve general practice and community pharmacy collaboration - Penny J. Lewis; Christopher J. Armitage; Darren M. Ashcroft; Tom Blakeman; Fay Bradley; Kyle Jarman; Mark Jeffries; Rebecca Morris; Denham Phipps; Andrea D. Short; Steven D. Williams (PLoS ONE, 2025)
Poor communication is a key causal factor of medication safety incidents. Collaboration between community pharmacy (CP) and general practice (GP) staff is essential but hindered by multiple barriers. This study applied an Experience-Based Co-Design (EBCD) approach, incorporating Systems Thinking for Everyday Work (STEW), to develop interventions for improving collaboration and communication on medication safety across the GP-CP interface. A sequential study design was undertaken, including: 1) an experience gathering phase to understand the communication of medication safety issues across the GP-CP interface, involving online focus groups and interviews with 27 GP and CP staff; and 2) two online EBCD workshops with 21 participants, including patients and primary care staff, to generate and prioritise interventions for improving medication safety communication and collaboration. Focus groups, interviews and workshops were audio-recorded, transcribed, and thematically analysed. Three key touchpoints for communication and collaboration on medication safety issues were identified: medication errors, medication changes, and potential patient safety concerns. An absence of shared communication approaches and the prioritisation of medication safety issues, one way communication tools, lack of understanding of professional roles and of incident reporting processes were barriers to communication and collaboration. Facilitators included GP pharmacist-community pharmacist relationships, face-to-face interactions and staff continuity. Five key interventions were suggested: development/modification of an electronic two-way communication tool between GP and CP; centralisation and sharing of patient records; interprofessional education; co-location of general practices and community pharmacies; and a toolkit for improving medication safety across the GP-CP interface. Participants agreed that a toolkit to address key communication and collaboration issues arising at multiple touchpoints should be prioritised for development and discussions led to refinement of ideas and production of a toolkit blueprint. Further research is required to refine toolkit resources, establish an implementation pathway, and evaluate its effectiveness to support adoption and improvements in medication safety.